2016
DOI: 10.1371/journal.pone.0156267
|View full text |Cite|
|
Sign up to set email alerts
|

Trunk Stability, Trunk Strength and Sport Performance Level in Judo

Abstract: Although trunk muscle function has been suggested to be a determinant of judo performance, its contribution to high-level performance in this sport has been poorly studied. Therefore, several tests were used to assess the differences in trunk muscle function between 11 international and 14 national level judo practitioners (judokas). Trunk strength and endurance were assessed using isokinetic tests and core stability was assessed using two protocols: 1) sudden loading, to assess trunk responses to unexpected e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 20 publications
(25 reference statements)
1
65
0
8
Order By: Relevance
“…Two protocols were performed to evaluate different trunk stability parameters in the following order [13]: 1) sudden loading protocol to assess trunk responses to external, quick and unexpected perturbations in different directions; 2) stable and unstable sitting protocol to assess the ability to control trunk posture and motion while sitting. Both protocols were performed in seated position with leg movement restriction to reduce lower limb influence and thus to focus the stability analysis on the trunk structures.…”
Section: Methodsmentioning
confidence: 99%
“…Two protocols were performed to evaluate different trunk stability parameters in the following order [13]: 1) sudden loading protocol to assess trunk responses to external, quick and unexpected perturbations in different directions; 2) stable and unstable sitting protocol to assess the ability to control trunk posture and motion while sitting. Both protocols were performed in seated position with leg movement restriction to reduce lower limb influence and thus to focus the stability analysis on the trunk structures.…”
Section: Methodsmentioning
confidence: 99%
“…But, in contrast to leg muscles, the trunk extensor muscles have a limited role in cycling, and the effect of cycling on the aerobic responses of the trunk muscles to sustained contraction is unknown. On the other hand, judo involves intensive use of back muscles [2]. Judokas thus present greater trunk muscle strength and endurance, even compared to cyclists [20].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, lower-body maximal strength and power training can improve spinal musculature strength [38]. Specifically, Barbado et al [17] demonstrated that international judokas express significantly higher trunk extensor strength compared to their national-level counterparts. As such, it can be reasonably concluded that judokas should possess a high level of lower-body strength and power which may allow for both improved spinal stability and enable them to express greater rotational power during uchi mata techniques.…”
Section: Discussionmentioning
confidence: 99%
“…For example, greater upper-body anaerobic peak and mean power, and specific technical skill performance (achieving more throws in the allotted time) in the special judo fitness test (SJFT), were noted for more successful compared to less successful adult judokas. Additionally, Barbado et al [17] reported greater trunk extensor strength for more successful compared with less successful adult judokas. However, despite the importance of trunk strength for the optimal execution of throwing techniques (e.g., Uchi mata), evidence regarding upper-body strength and power remains limited when examining this sport [18], particularly with regards to junior judokas.…”
Section: Introductionmentioning
confidence: 99%